Correlation Between the Inferior Vena Cava/Aorta (Ivc/Ao) Ratio and Serum Lactate Levels in Children With Renal Disorder - Hakim DDL; Widiasta A; Rachmadi D; Rahayunigsih SE; Apandi PR; Adrizain R; Martiano MRA (International Journal of Nephrology and Renovascular Disease)
Dzulfikar Djalil Lukmanul Hakim,1 Ahmedz Widiasta,2 Dedi Rachmadi,2 Sri Endah Rahayunigsih,3 Putria Rayani Apandi,3 Riyadi Adrizain,4 Muhamad Rinaldhi Akbar Martiano5 1Division of Emergency and Intensive Care, Department of Child Health, Faculty of Medicine, Universitas Padjadjaran Dr. Hasan Sadikin, Bandung, Indonesia; 2Division of Nephrology, Department of Child Health, Faculty of Medicine, Universitas Padjadjaran Dr. Hasan Sadikin, Bandung, Indonesia; 3Division of Cardiology, Department of Child Health, Faculty of Medicine, Universitas Padjadjaran Dr. Hasan Sadikin, Bandung, Indonesia; 4Division of Infection, Department of Child Health, Faculty of Medicine, Universitas Padjadjaran Dr. Hasan, Sadikin, Bandung, Indonesia; 5Department of Pediatric, Faculty of Medicine, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Dzulfikar Djalil Lukmanul Hakim, Division of Emergency and Intensive Care, Department of Child Health, Faculty of Medicine, Universitas Padjadjaran Dr. Hasan Sadikin, Jl. Pasteur No. 38, Pasteur, Bandung, Sukajadi, 40161, Tel +62 681221594677, Email dzulfikar.djalil@unpad.ac.idBackground: Acute kidney injury (AKI) is common in critically ill children in the PICU, with incidence rates from 2.5% to 58%, impacting mortality and hospital duration. Early AKI detection is vital, but conventional hemodynamic monitoring often lacks specificity. This study investigates the relationship between the inferior vena cava/aortic (IVC/Ao) ratio and serum lactate levels as non-invasive indicators of renal hemodynamics and tissue perfusion in children. Understanding these parameters could improve early diagnosis, aid clinical decisions, and enhance outcomes for pediatric AKI patients, offering an accessible monitoring method for clinicians.Methods: This cross-sectional study involved 48 pediatric patients aged 5– 18 years showing Pediatric Early Warning Score (PEWS) ≥ 3 and diagnosed with renal disorders. Patients were admitted to the emergency department, high care unit, PICU, and pediatric ward at Dr. Hasan Sadikin Hospital, Bandung, between May and August 2023. AKI was diagnosed using pRIFLE or KDIGO criteria. The IVC/Ao ratio was assessed via transabdominal USG, and serum lactate levels were measured. Spearman correlation analysis was conducted to assess their relationship.Results: The median (IQR) IVC/Ao ratio was 0.91 (0.70– 1.10), and serum lactate levels were 1.5 (1.1– 2.4) mmol/L. Spearman correlation analysis revealed a negative correlation between the IVC/Ao ratio and serum lactate (rho = − 0.65, p < 0.001).Conclusion: A decrease in the IVC/Ao ratio correlates with an increase in serum lactate levels in children with AKI.Keywords: acute kidney injury, children, IVC/Ao, serum lactate